Assessment of potential land suitability for rainfed wheat production using GIS and multi criteria decision analysis in the Southwestern parts of Ethiopia - Bacha Gebissa Negeri; Bai Xiuguang; Mitiku Badasa Moisa (PLoS ONE, 2025)
Wheat production in Ethiopia is vital for improving food security, boosting the national economy, and achieving self-sufficiency in food consumption. The present study aims to assess the potential land suitability for rainfed wheat (Triticum aestivum L.) production by using Geographic Information System and multi criteria decision analysis in southwestern parts of Ethiopia. Biophysical data, including land use and land cover (LULC), soil drainage, soil texture, soil depth, proximity to markets and roads, land surface temperature, slope, rainfall, and elevation, were used. In addition, different software tools, such as ArcGIS 10.3, ERDAS Imagine 2015, IDRISI Selva 17, and ArcSWAT were applied. The results revealed that approximately 177.1 km² (1.3%) of the study area was classified as highly suitable, 5375.2 km² (38.2%) as moderately suitable, 7,246.0 km² (51.5%) as marginally suitable, and 1235.1 km² (8.8%) as currently not suitable for rainfed wheat cultivation. Furthermore, out of the 23 districts analyzed, Sayo Nole and Bedelle Zuriya were identified as highly suitable for wheat production, with an area of 32.7km2 and 23.3km2 respectively. Therefore, the study recommends that future study research investigate additional other ecological parameters, such as soil PH, lime, gypsum, salinity, alkalinity and socio-economic data, which were not included in the present study.